"Have You Not Heard of Florida?" Jean Ribault, Thomas Stukeley, and the Dream of England's First Overseas Colony. Issue 3 (December 2019) - DeCoster, Jonathan
Abstract: English overseas colonialism is generally traced to the anti-Catholic and anti-Spanish ideologies of Richard Hakluyt, Humphrey Gilbert, and other exponents in the 1570s and 1580s. This article puts Florida at the forefront of English colonialism by taking seriously Thomas Stukeley's proposed colonisation expedition in 1563. The focus on the 1560s reveals how a dynastic rivalry with France, rather than a religious rivalry with Spain, gave birth to England's first colonial impulse. Jean Ribault, well known as the founder of French Florida, serves as the connecting link between Florida and England. His previously unappreciated role in European diplomacy unwittingly turned his fledgling colony into a pawn to be traded among France, Spain, and England. Furthermore, Queen Elizabeth's interest in joining the race for colonies may have been fuelled more by her desire to regain Calais from the French than to plant settlers in America. But while her motives may well have been cynical, the English public for the first time began to see itself as a colonising people. The end result was that Florida not only emerged as part of the fountainhead of English colonialism, but also came to play an important role in European politics.